2017
DOI: 10.1016/j.foodres.2017.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharides integrity after atmospheric cold plasma and high-pressure processing of a functional orange juice

Abstract: In this study, the effect of atmospheric pressure cold plasma and high-pressure processing on the prebiotic orange juice was evaluated. Orange juice containing 7g/100g of commercial fructooligosaccharides (FOS) was directly and indirectly exposed to a plasma discharge at 70kV with processing times of 15, 30, 45 and 60s. For high-pressure processing, the juice containing the same concentration of FOS was treated at 450MPa for 5min at 11.5°C in an industrial equipment (Hyperbaric, model: 300). After the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 43 publications
1
28
0
5
Order By: Relevance
“…However, the stabilization mechanisms associated with HPP are mainly based on mechanical energy [ 24 ]. Almeida et al [ 12 ] reported a FOS hydrolysis of 21.4% in samples of FOS-enriched orange juice subjected to non-thermal HPP at 450 MPa for 5 min at 11.5 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stabilization mechanisms associated with HPP are mainly based on mechanical energy [ 24 ]. Almeida et al [ 12 ] reported a FOS hydrolysis of 21.4% in samples of FOS-enriched orange juice subjected to non-thermal HPP at 450 MPa for 5 min at 11.5 °C.…”
Section: Resultsmentioning
confidence: 99%
“…They are widely distributed in a variety of plants as a storage carbohydrate [ 8 ]. Several products have been enriched with these prebiotic compounds to increase their functionality like semi-hard cheese [ 9 ], fermented sausages [ 10 ], Greek yogurt [ 11 ], fruit juices [ 12 ], infant formulas [ 13 ], and many others. Recently Brazilian ginseng ( Pfaffia glomerata ) roots were recognized as a new source of short-chain FOS, including 1-kestose, nystose, and fructofuranosylnystose with up to 8.8 g/100 g of prebiotic carbohydrates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al. () compared the degradation of fructooligosaccharides in water and orange juice after NTP treatment. It was observed that the fructooligosaccharides degradation was more in orange juice than in water.…”
Section: Ntp–liquid Interactions In Foodmentioning
confidence: 99%
“…Berardinelli et al (2016) also stated that the inactivation efficiency of PAW varies with respect to the kind of vegetables. Almeida et al (2017) compared the degradation of fructooligosaccharides in water and orange juice after NTP treatment. It was observed that the fructooligosaccharides degradation was more in orange juice than in water.…”
Section: Ntp-liquid Interactions In Foodmentioning
confidence: 99%
“…El PF se propone como una tecnología de conservación no térmica con alto potencial para prolongar la vida de anaquel de los alimentos (Liao et al, 2020;Pan et al, 2019a;Sonawane et al, 2020;Ziuzina et al, 2014), basándose en la descontaminación microbiana (Bermúdez-Aguirre et al, 2013;Bourke et al, 2018;Mandal et al, 2018;Misra et al, 2016;Niemira y Sites, 2008;Pasquali et al, 2016;Patil et al, 2016;Sonawane et al, 2020;Stoica et al, 2014), y la inactivación enzimática (Almeida et al, 2017;Bourke et al, 2017;Surowzky et al, 2013;Ozen y Singh, 2020;Pan et al, 2019b).…”
Section: Aplicación Del Plasma Frío Como Tecnología De Conservación Alimentariaunclassified